What's in a Task? Complications in the Study of the Task-Unrelated-Thought Variety of Mind Wandering. (May 2020) - Murray, Samuel; Krasich, Kristina; Schooler, Jonathan W.; Seli, Paul
In recent years, the number of studies examining mind wandering has increased considerably, and research on the topic has spread widely across various domains of psychological research. Athough the term mind wandering has been used to refer to various cognitive states, researchers typically operationalize mind wandering in terms of task-unrelated thought (TUT). Research on TUT has shed light on the various task features that require people's attention and on the consequences of task inattention. Important methodological and conceptual complications do persist, however, in current investigations of TUT. We argue that these complications may be dampening the development of a more nuanced scientific account of TUT. In this article, we outline three of the more prominent methodological and conceptual complications in the literature on TUT and discuss potential directions for researchers to take as they move forward in their investigations of TUT.